Bitemporal Blindness in Traumatic Head Injury - Wahab, Nurul Zulaikha; Tai, Evelyn; Wan Hitam, Wan Hazabbah; Sonny Teo Abdullah, Khairy Shamel (IIUM Medical Journal Malaysia, 2022)
We report a case of isolated bitemporal hemianopia in traumatic chiasmal syndrome. A 20-year-old male motorcyclist was brought unconscious into the emergency department after an alleged accident involving a horse-drawn vehicle. He was intubated for three days. Computed topography of the brain revealed bifrontal and facial bone fractures, associated with subarachnoid haemorrhage. He underwent frontal bone and facial bone reconstruction. Three weeks later, patient complained of left eye blurred vision. On examination, the visual acuity was 6/7.5 in the right eye and 6/12 in the left eye, with a left relative afferent pupillary defect. Visual field charting showed complete bitemporal hemianopia. Over the next six months, the visual acuity of the left eye worsened to 6/45, while the field defect remained static. Bitemporal hemianopia in traumatic chiasmal syndrome is a rare complication of severe head injury. A history of trauma should always be elucidated in patients with visual field defects.